THE ARAB SPRING AND CIVIL-MILITARY RELATIONS: A PRELIMINARY ASSESSMENT - Segell, Glen (Scientia Militaria - South African Journal of Military Studies, 2013)
The ‘Arab Spring’ refers to the wave of civil unrest that covered countrieswith predominant Moslem populations in North Africa, the Middle East and theArabian Peninsula, which started late 2010 in Tunisia. The unrests quickly spreadacross the region, giving rise to the notion of a single inter-related event. However,the results and outcome in each country have been different. This is because eachand every country had its own unique political system and unique institutions ofstate with different relations between power elites. Two institutions of state hadprime importance in this political system. These were the executive and the military.In each there was only one important person, the state leader be he president, king,prime minister, emir or sheik or the chief of the armed forces. This article describesthat a major cause for the different results and outcomes in each country wasdetermined by the prevailing relations between them, i.e. the civil-military relations.